METHODOLOGICAL ASPECTS OF RESEARCH USING ACTIVATED SOLUTIONS COAGULANT IN THE WATER (Municipal economy of cities. Series: «Economy science», 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 8.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; color: #333333; mso-ansi-language: EN; mso-fareast-language: UK; mso-bidi-language: AR-SA;" lang="EN">Methodological<span style="font-size: 8.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; color: #333333; mso-ansi-language: EN; mso-fareast-language: UK; mso-bidi-language: AR-SA;" lang="EN"> aspects of studies using activated solutions of coagulants in water treatment. The technique of the experiments, the attention paid to assessing the reliability of research results and their reproducibility and the definition of a confidence interval of the research.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>